The Resilience of Latin American Regionalism: A~Neofunctionalist Perspective - Detlef Nolte; Brigitte Weiffen (Politische Vierteljahresschrift, 2024)
Latin America has seen both recurrent crises and a surprising resilience of its regional organizations. This article explores how different approaches have attempted to explain this seemingly paradoxical record. Combining insights from European Union (EU) studies and comparative regionalism, we ask whether neofunctionalism as a theoretical approach developed for the study of the EU can travel across the Atlantic and enrich the analysis of Latin American regionalism. Neofunctionalist theorists posited that functional spillover could lead to politicization and subsequent deepening of regional integration. But while spillover has been the engine of European integration, it has never been a real option in Latin America. Past applications of neofunctionalist approaches to Latin American regionalism have therefore above all revealed its limitations. Comparative regionalism approaches fared better in that they identified characteristics that account for the repeated crises of Latin American regional organizations. However, this article suggests that the "second-best" strategies mentioned in neofunctionalist analyses, such as encapsulation, spill-around, or even spillback, can help explain the resilience of regionalism in Latin America. While those strategies posed an obstacle to deeper integration, as shown by classical neofunctionalist studies, we draw on a set of case studies to illustrate that Latin American regionalism survived through expansion (spill-around) rather than deepening (spillover), as well as through encapsulation and, in some cases, even spillback. A new reading of neofunctionalism therefore helps to explain the resilience of Latin American regionalism under adverse conditions. – – Regionalorganisationen in Lateinamerika zeichnen sich sowohl durch wiederkehrende Krisen als auch eine überraschende Widerstandsfähigkeit aus. In diesem Artikel werden unterschiedliche Ansätze zur Erklärung dieser scheinbar paradoxen Bilanz untersucht. Wir kombinieren Erkenntnisse aus der europäischen Integrationsforschung und der vergleichenden Regionalismusforschung und werfen die Frage auf, ob der Neofunktionalismus, der für die Analyse der Europäischen Union (EU) entwickelt wurde, jenseits des Atlantiks auf die Analyse des lateinamerikanischen Regionalismus anwendbar ist. Neofunktionalistische Theoretiker postulierten, dass ein funktionaler Spillover üblicherweise zur Politisierung und anschließenden Vertiefung der regionalen Integration führe. Doch während Spillover-Effekte der Motor der europäischen Integration waren, traten sie in Lateinamerika nicht auf. Frühere Versuche der Anwendung neofunktionalistischer Ansätze auf den lateinamerikanischen Regionalismus zeigten daher vor allem dessen Grenzen auf. Die vergleichende Regionalismusforschung schnitt insofern besser ab, als sie Ursachen für die wiederholten Krisen lateinamerikanischer Regionalorganisationen zu identifizieren vermochte. Demgegenüber legt dieser Artikel nahe, dass die in neofunktionalistischen Analysen erwähnten "zweitbesten" Strategien, wie Verkapselung (Encapsulation), Expansion (Spill-around) oder sogar Spillback, zur Erklärung der Resilienz des Regionalismus in Lateinamerika beitragen können. Während laut klassischer neofunktionalistischer Studien diese Strategien einer vertieften Integration im Wege standen, veranschaulichen wir mit einer Reihe von Fallstudien, dass der lateinamerikanische Regionalismus eher durch Expansion (Spill-around) als durch Vertiefung (Spillover) überlebte sowie durch Verkapselung und in einigen Fällen sogar durch Spillback. Eine neue Lesart des Neofunktionalismus trägt daher dazu bei, die Resilienz des lateinamerikanischen Regionalismus unter widrigen Bedingungen zu erklären.
Keywords: 320; Comparative regionalism; Crisis; Latin America; Neofunctionalism; Regional organizations; Vergleichender Regionalismus; Krise; Lateinamerika; Neofunktionalismus; Regionalorganisationen